2003
DOI: 10.1093/emboj/cdg546
|View full text |Cite
|
Sign up to set email alerts
|

High throughput virus-induced gene silencing implicates heat shock protein 90 in plant disease resistance

Abstract: Virus‐induced gene silencing was used to assess the function of random Nicotiana benthamiana cDNAs in disease resistance. Out of 4992 cDNAs tested from a normalized library, there were 79 that suppressed a hypersensitive response (HR) associated with Pto‐mediated resistance against Pseudomonas syringae. However, only six of these clones blocked the Pto‐mediated suppression of P.syringae growth. The three clones giving the strongest loss of Pto resistance had inserts corresponding to HSP90 and also caused loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
472
0
6

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 510 publications
(489 citation statements)
references
References 53 publications
11
472
0
6
Order By: Relevance
“…So far, genetic approaches have identified relatively few components required for R gene function in plants [5]. A highly conserved protein class, the heat-shock proteins, has now been added to the list and work on these proteins promises to provide fresh insights to the molecular mechanics of the pathogen recognition process [6][7][8][9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…So far, genetic approaches have identified relatively few components required for R gene function in plants [5]. A highly conserved protein class, the heat-shock proteins, has now been added to the list and work on these proteins promises to provide fresh insights to the molecular mechanics of the pathogen recognition process [6][7][8][9].…”
mentioning
confidence: 99%
“…An indication that the former might be true is the observation that RPM1 steady-state levels are greatly decreased or undetectable in non-challenged rar1 or hsp90.2 mutant backgrounds [7,19]. The role of SGT1 in R protein function is likely to be different, because RX protein accumulation was impaired following NbHSP90 silencing but unaffected upon NbSGT1 silencing [9].…”
mentioning
confidence: 99%
“…The function of these proteins in disease resistance responses have been extensively investigated previously using mutant analyses Chandra-Shekara et al, 2004;Hubert el al., 2003;Lu et al, 2003;Shirasu et al, 1999;Takahashi et al, 2003) and by virus induced gene silencing (VIGS) analyses in several plant species (Bhattarai et al, 2007;de la Fuente van Bentem et al, 2005;Leister et al, 2005;Liu et al, 2004;Scofield et al, 2005). The data from these studies revealed differing specificities for these proteins in diverse NB-LRR-mediated resistance responses.…”
Section: Discussionmentioning
confidence: 99%
“…For example, RAR1 and SGT1 are required for MLA6-and MLA12-, but not MLA1-, mediated resistance (Azevedo et al, 2002). Tobacco N, a Tobacco mosaic virus resistance protein, and wheat Lr21, a Puccinia triticina resistance protein, require each of the proteins for the initiation of immune responses against pathogens (Liu et al, 2004;Lu et al, 2003;Peart et al, 2002;Scofield et al, 2005). The function of each of these chaperone proteins has not yet been fully explored in rice immune responses governed by NB-LRRs.…”
Section: Discussionmentioning
confidence: 99%
“…In this approach, cDNA libraries are constructed within virus expression vectors and gene function to be assessed by screening infected plant hosts for phenotypic or metabolic changes measured by various input and output focused screening assays. TMV and PVX VIGS vectors were the first to employed in this manner in the dicot N. benthamiana, with BSMV used shortly after in the monocot barley [84,100]. Since these first reports, vector systems for functional genomics have continued to be refined and optimized in an expanding number of hosts [18,87], including systems amenable for high throughput screens in monocots based on BSMV [101,102].…”
Section: Use Of Transient Expression Vectors As Functional Gene Discomentioning
confidence: 99%